Vinyl chloride resin particle, and vinyl chloride resin composition
Vinyl chloride resin particles with a plate-like inorganic filler on their surface address the issue of unstable sol viscosity over time, providing excellent storage stability and performance for automotive underbody coatings and sealants.
Patent Information
- Application Number
- JP2024003000
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-22
- Filing Date
- 2024-01-12
- Publication Date
- 2025-04-04
AI Technical Summary
Existing vinyl chloride resin technologies fail to provide stable sol viscosity over time, particularly in applications like automobile underbody coatings and sealants, where long-term stability is crucial.
Vinyl chloride resin particles with a specific plate-like inorganic filler on their outer surface, which control the absorption of plasticizers and maintain excellent storage stability even at high temperatures.
The vinyl chloride resin particles exhibit minimal change in sol viscosity over time, ensuring excellent storage stability and performance in high-temperature environments, particularly for automotive underbody coatings and sealants.
Smart Images

Figure 2025051565000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to novel vinyl chloride resin particles having a specific inorganic filler present on the outer surface. In particular, the presence of the specific inorganic filler on the outer surface results in little change in viscosity over time of the sol, which is the composition when kneaded with a plasticizer, and furthermore has excellent storage stability in environments of 40°C or higher. Therefore, the present invention relates to vinyl chloride resin particles, vinyl chloride resin compositions and uses thereof that are useful for automobile underbody coatings and automobile sealants. [Background technology]
[0002] Plastisols, which are prepared by dispersing polymer particles in a plasticizer medium, are used in a wide variety of industrial fields, such as automobile undercoats, automobile body sealers, wallpaper, carpet backing materials, flooring materials, paints, and toys.
[0003] A vinyl chloride resin is an example of a plastisol that is widely used. Generally, vinyl chloride resins are prepared by kneading them with plasticizers, fillers, stabilizers, and other compounding agents to prepare vinyl chloride sols, which are then used in a variety of molded products such as wallpaper, carpet tiles, and gloves by various molding methods.
[0004] Furthermore, for applications requiring low processing temperatures, vinyl chloride / vinyl acetate copolymer resins, in which vinyl chloride is copolymerized with vinyl acetate, are known, which have excellent gelling and melting properties that enable mechanical strength to be obtained even at relatively low temperatures. Furthermore, as a measure for long-term storage stability from the preparation of PVC sol to processing, there is a demand for vinyl chloride resins that exhibit little change in sol viscosity over time.
[0005] As a method for producing a vinyl chloride resin with little change in sol viscosity over time, a method for producing a vinyl chloride resin for paste processing using a specific surfactant has been proposed (see, for example, Patent Document 1).
[0006] Additionally, a vinyl chloride resin composition has been proposed in which a specific compound is blended with a paste vinyl vinyl sol (see, for example, Patent Document 2). [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Japanese Patent Application Publication No. 06-056915 [Patent Document 2] JP 2010-241977 A Summary of the Invention [Problem to be solved by the invention]
[0008] However, the vinyl chloride resin obtained by the method proposed in Patent Document 1 does not satisfy market demands when used in applications that require strict stability against changes in sol viscosity over time, such as automobile undercoats, automobile sealants, etc. In addition, while the method proposed in Patent Document 2 can provide a vinyl chloride sol with relatively little change in viscosity over time, long-term viscosity stability has not been examined.
[0009] It is therefore an object of the present invention to provide vinyl chloride resin particles which exhibit extremely little change in sol viscosity over time and have excellent properties for use as a coating agent, particularly for automobile underbody coatings and automobile sealants, and uses thereof. [Means for solving the problem]
[0010] Means for Solving the Problems The present inventors have conducted extensive research into the above-mentioned problems and have found that vinyl chloride resin particles having specific plate-like inorganic fillers present on the outer surface thereof have excellent storage stability when made into a vinyl chloride resin sol containing a plasticizer, and have excellent physical properties as a coating agent, particularly for use in automobile underbody coatings and automobile sealants, thereby completing the present invention.
[0011] That is, the present invention relates to vinyl chloride resin particles having an inorganic filler present on the outer surface, characterized in that the inorganic filler is a plate-like inorganic filler having a particle size of 60 to 7000 nm and an aspect ratio of 20 to 2000.
[0012] The present invention will be described in detail below.
[0013] The vinyl chloride resin particles of the present invention have a plate-like inorganic filler on their outer surface, and the presence of the plate-like inorganic filler on the outer surface makes it possible to control plasticizer absorption and provides excellent storage stability, and it is particularly preferable that the plate-like inorganic filler is provided as a surface coating layer. The coating layer not only includes a completely coated state, but also includes a layer having some voids, etc., as long as it provides the effects of the present invention.
[0014] The vinyl chloride resin constituting the vinyl chloride resin particles of the present invention may be any one that belongs to the category generally called vinyl chloride resin, for example, in addition to vinyl chloride resin which is a homopolymer, vinyl chloride-vinyl acetate copolymer resin, vinyl chloride-butyl acrylate copolymer resin, vinyl chloride-butyl methacrylate copolymer resin, vinyl chloride-ethyl acrylate copolymer resin, vinyl chloride-ethyl methacrylate copolymer resin, vinyl chloride-vinyl propionate copolymer resin, etc. can be mentioned, among which, vinyl chloride-vinyl acetate copolymer resin is preferable because it is excellent in low-temperature processability during processing, and particularly vinyl chloride-vinyl acetate copolymer resin with a vinyl acetate residue content of 1 to 20 wt% is preferable. In addition, the particle size at that time may be any one, and in particular, it is preferable that it is 0.05 to 100 μm in average particle size, and more preferably 0.1 to 50 μm in average particle size, because it is excellent in balance between handling, physical properties and molding processability. In addition, as a method for measuring the particle size, average particle size, etc. in the present invention, for example, a method using a disk centrifugal particle size distribution measuring device can be mentioned. The vinyl chloride resin may be any of those called SUS vinyl chloride resins and vinyl chloride resins for paste processing, and vinyl chloride resins for paste processing are preferable because they can be molded into, for example, coats, sealants, wallpapers, gloves, etc. in a (plasti)sol state, which is a composition containing a plasticizer.
[0015] The plate-like inorganic filler constituting the vinyl chloride resin particles of the present invention may be any that belongs to the category called plate-like inorganic filler, for example, smectite clay minerals such as bentonite, montmorillonite, saponite, hectorite, beidellite, nontrilonite, sauconite, etc.; plate-like alumina, kaolin, hydrotalcite, vermiculite, halloysite, swelling mica, etc., and may be either natural or synthetic. Among them, montmorillonite, bentonite, saponite, hectorite, plate-like alumina, kaolin, and hydrotalcite are preferable because they are vinyl chloride resin particles with excellent storage stability.
[0016] The plate-like inorganic filler is an inorganic filler having a particle size of 60 to 7000 nm, and is particularly excellent in storage stability when made into a vinyl chloride resin sol, so it is preferably in the range of 60 to 4000 nm. Here, if the particle size is less than 60 nm or more than 7000 nm, the viscosity increase change when made into a sol becomes significant, resulting in poor storage stability. In addition, the plate-like inorganic filler is an inorganic filler having an aspect ratio in the range of 20 to 2000, and is particularly excellent in storage stability, so it is preferably in the range of 30 to 500 nm. Here, if the aspect ratio is less than 20 or more than 2000, the effect of suppressing viscosity increase when made into a sol is poor.
[0017] The content of the plate-like inorganic filler in the vinyl chloride resin particles of the present invention is not limited as long as it can exhibit the effect of suppressing thickening when made into a sol and it is possible to prepare particles having the plate-like inorganic filler on the outer surface. In particular, it is preferable that the content of the plate-like inorganic filler is 0.1 to 30 parts by weight, particularly 0.1 to 25 parts by weight, and further 0.3 to 25 parts by weight, relative to 100 parts by weight of the vinyl chloride resin, since this facilitates drying of the latex when made into particles and provides an excellent effect of suppressing thickening.
[0018] As the method for producing the vinyl chloride resin particles of the present invention, any method can be used as long as it is possible to produce the vinyl chloride resin particles. For example, a plate-like inorganic filler is dispersed in a latex or emulsion containing vinyl chloride resin particles obtained by a vinyl chloride resin polymerization method such as suspension polymerization, emulsion polymerization, microsuspension polymerization, seed emulsion polymerization, or seed microsuspension polymerization, and the like, and the solvent, water, etc. are removed by a method such as drying, thereby producing vinyl chloride resin particles having a plate-like inorganic filler on the outer surface. When producing vinyl chloride resin particles, a polymerization initiator, deionized water, an emulsifier, a buffer, and an emulsification aid such as a higher alcohol, if necessary, can be appropriately used. The additives may be contained in the vinyl chloride resin particles as long as they achieve the object of the present invention.
[0019] The polymerization initiator may be any one that falls within the category of polymerization initiators, and examples of the polymerization initiator include water-soluble polymerization initiators such as potassium persulfate and ammonium persulfate; oil-soluble polymerization initiators such as azo compounds such as azobisisobutyronitrile, lauroyl peroxide, t-butyl peroxypivalate, diacyl peroxide, peroxy ester, peroxy dicarbonate, etc. When performing a seed microsuspension polymerization method, seed particles (seeds) containing an oil-soluble initiator may be used.
[0020] As the emulsifier, one or more of the conventionally known emulsifiers that can be used include alkyl sulfate salts such as sodium lauryl sulfate and myristyl sulfate; alkylaryl sulfonates such as sodium dodecylbenzenesulfonate and potassium dodecylbenzenesulfonate; sulfosuccinates such as sodium dioctyl sulfosuccinate and sodium dihexyl sulfosuccinate; fatty acid salts such as ammonium laurate and potassium stearate; anionic emulsifiers such as polyoxyethylene alkyl sulfate salts and polyoxyethylene alkylaryl sulfate salts; sorbitan esters such as sorbitan monooleate and polyoxyethylene sorbitan monostearate; polyoxyethylene alkylphenyl ethers; and nonionic emulsifiers such as polyoxyethylene alkyl esters.
[0021] Examples of the buffer include alkali metal monohydrogen phosphate, alkali metal dihydrogen phosphate, potassium hydrogen phthalate, sodium hydrogen carbonate, boric acid-caustic potassium solution, and the like.
[0022] Examples of emulsifying aids that are used if necessary include higher alcohols such as cetyl alcohol and lauryl alcohol; higher fatty acids such as lauric acid, palmitic acid and stearic acid; esters thereof; aromatic hydrocarbons, higher fatty acid hydrocarbons, and halogenated hydrocarbons such as chlorinated paraffin.
[0023] As a polymerization method of vinyl chloride resin, which is a component of the vinyl chloride resin particles of the present invention, particularly a more specific polymerization method of vinyl chloride resin for paste processing, there are, for example, a microsuspension polymerization method in which vinyl chloride monomer, emulsifier, oil-soluble polymerization initiator, and emulsification aid such as aliphatic higher alcohol are added to deionized water, mixed and dispersed with a homogenizer or the like, and then polymerization is performed under gentle stirring; a seed microsuspension polymerization method using seed particles (seeds) containing an oil-soluble polymerization initiator obtained by the microsuspension polymerization method; a seed emulsion polymerization method in which emulsion polymerization is performed using particles obtained by an emulsion polymerization method in which vinyl chloride monomer is polymerized with deionized water, a surfactant, and a water-soluble polymerization initiator under gentle stirring as seeds, and the like, and at that time, for example, the polymerization temperature is set to 20 to 80 ° C., and vinyl chloride resin latex can be obtained. Then, a dispersion in which a plate-shaped inorganic filler is dispersed in the vinyl chloride resin latex produced by these polymerizations is spray-dried, and if necessary, pulverized to obtain vinyl chloride resin particles.
[0024] The dryer used to produce the vinyl chloride resin particles may be any commonly used dryer, such as a spray dryer (specific examples include various spray dryers described in FIG. 4.10 on page 121 of "SPRAY DRYING HANDBOOK" (K. Masters, 3rd Edition, 1979, published by Georgegodwin Limited)). There are no particular limitations on the drying air inlet temperature and drying air outlet temperature, and the drying air inlet temperature is generally 80 to 210°C, and the drying air outlet temperature is generally 45 to 75°C. It is more preferable that the drying air inlet temperature is 160 to 210°C, and the drying air outlet temperature is 55 to 75°C.
[0025] Since the vinyl chloride resin particles of the present invention have a plate-like inorganic filler on their outer surface, it is possible to control the absorption of the plasticizer when the particles are made into a sol, which is a composition containing a plasticizer, and it is possible to suppress the thickening of the sol, and it is possible to provide a sol with excellent storage stability. When the particles are made into a vinyl chloride resin composition as a sol, it is preferable that the amount of the plasticizer is 50 to 200 parts by weight, and particularly 80 to 150 parts by weight, per 100 parts by weight of the vinyl chloride resin particles, since this makes it easier to provide a sol with excellent processability and moldability.
[0026] The plasticizer may be any plasticizer that is in the category of vinyl chloride resin plasticizers, and examples of the plasticizer include phthalates such as bis(2-ethylhexyl) phthalate (sometimes abbreviated as DOP), diisononyl phthalate, diisodecyl phthalate, and dibutyl phthalate; adipates such as 2-ethylhexyl adipate and diisononyl adipate; trimellitates such as tri(2-ethylhexyl) trimellitate, triisodecyl trimellitate, and tri-n-octyl trimellitate; Examples of suitable organic solvents include phosphates such as tri(2-ethylhexyl) phosphate, tricresyl phosphate, and trixylenyl phosphate; benzoate esters such as diethylene glycol dibenzoate and dipropylene glycol dibenzoate; citrate esters such as acetyl tributyl citrate; sulfonate esters such as alkylsulfonate phenyl ester; and other polyester plasticizers, sebacic acid esters, magellic acid esters, maleic acid esters, and epoxidized vegetable oils.
[0027] In addition, when preparing a vinyl chloride resin composition, a filler may be included as necessary, and in that case, since a sol having excellent properties is obtained, it is preferable that the filler is included in an amount of 1 to 150 parts by weight per 100 parts by weight of vinyl chloride resin particles. Examples of the filler include calcium carbonate, diatomaceous earth, magnesium carbonate, titanium oxide, etc., and in that case, the filler may be surface-treated.
[0028] Furthermore, when preparing a vinyl chloride resin composition, additives which are usually added to vinyl chloride sols, such as antioxidants, flame retardants, diluents, lubricants, ultraviolet absorbers, colorants such as pigments, surfactants, antistatic agents, etc. may be added within the range not exceeding the object of the present invention, and the amounts of these additives may be within the ranges generally used.
[0029] The vinyl chloride resin particles of the present invention can provide a vinyl chloride resin composition having excellent storage stability when blended with a plasticizer or the like, and can be used in a variety of applications, such as wallpaper, carpet tiles, gloves, coating agents, carpet backing materials, flooring materials, paints, and toys.
[0030] The composition is particularly suitable for use in seats, automobile underbody coatings, automobile sealants, and the like. Effect of the Invention
[0031] The vinyl chloride resin particles of the present invention exhibit little change in sol viscosity over time when kneaded with a plasticizer or the like, and have excellent storage stability, particularly in environments of 40°C or higher. They also exhibit excellent properties, particularly when used for automobile underbody coatings and automobile sealants. [Brief description of the drawings]
[0032] [Figure 1] FIG. 2 is a diagram showing elemental mapping of aluminum by TEM-EDS in a cross section of a thin film of the polyvinyl chloride resin particle obtained in Example 1. EXAMPLES
[0033] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these.
[0034] The methods for evaluating the vinyl chloride resin particles in the examples are described below.
[0035] <Vinyl acetate residue unit content> The vinyl acetate residue content (wt%) in the vinyl chloride-vinyl acetate copolymer resin for paste processing was measured by infrared absorption spectroscopy using a Fourier transform infrared spectrophotometer (manufactured by Shimadzu Corporation, product name IRAffinity-1). -1 The Abs. value of the absorption peak top due to CH in-plane bending near 1740 cm -1 The Abs. value of the absorption peak top due to C=O stretching in the vicinity was calculated using a separately measured calibration curve.
[0036] <Breaking elongation and breaking strength> A vinyl chloride resin composition sheet was prepared from the obtained vinyl chloride resin particles, and test pieces conforming to the JIS No. 3 dumbbell were prepared. Marked lines were drawn at 20 mm intervals in the center of the test pieces, which were then attached to a tensile testing device and pulled at a rate of 50 mm / min at 23°C. The elongation between the marks and the stress at break were measured, and the breaking elongation and breaking strength were calculated.
[0037] <Thickening rate (storage stability)> A vinyl chloride resin composition was prepared from the obtained vinyl chloride resin particles, and after storing it at 23°C for 24 hours, it was measured at a shear rate of 4 s using a viscoelasticity measuring device (manufactured by Anton Paar Japan, product name: MCR302). -1 The viscosity measured in the above step was regarded as the initial viscosity. Furthermore, after storing the vinyl chloride resin composition in an atmosphere of 40° C. for 7 days, the viscosity (β) was measured in the same manner as for the initial viscosity, and the viscosity increase rate (%) was calculated from this value and the initial viscosity (α) according to the following formula (1). Thickening rate (%)=((β-α) / α)×100 (1) <Elemental analysis of the surface of polyvinyl chloride resin particles> The obtained polyvinyl chloride resin particles were embedded in an embedding resin, carbon deposition was performed, and a platinum protective layer was applied in a FIB processing device (manufactured by Nippon FI Co., Ltd.; product name: Helios G4 UX). Then, a thin film cross section was prepared using an ion beam, and elemental analysis of the thin film cross section was performed using an energy dispersive X-ray spectrometer (EDS) with a field emission transmission electron microscope (manufactured by JEOL Ltd.; product name: JEM-ARM200F). Elemental mapping of aluminum was performed to observe the distribution of aluminum.
[0038] Synthesis Example 1 1m 3 In an autoclave, 360 kg of deionized water, 300 kg of vinyl chloride monomer, 10 kg of lauroyl peroxide, 30 kg of 15 wt% aqueous sodium dodecylbenzenesulfonate solution, and 1.5 kg of dodecyl mercaptan were charged, and circulated using a homogenizer for 2 hours. After homogenization, the temperature was raised to 45° C. to proceed with polymerization. After the pressure was reduced, the unreacted vinyl chloride monomer was recovered to obtain seed latex (a) having an average particle size of 0.60 μm and a solid content of 39 wt%.
[0039] Synthesis Example 2 1m 3 360 kg of deionized water, 300 kg of vinyl chloride monomer, 5.7 kg of lauroyl peroxide, and 30 kg of 15 wt% aqueous solution of sodium dodecylbenzenesulfonate were charged into a stainless steel autoclave, and the mixture was circulated for 3 hours using a homogenizer for homogenization, after which the temperature of the reaction system was raised to 45° C. to initiate polymerization. After the pressure of the polymerization system was reduced, the unreacted vinyl chloride monomer was recovered, and a vinyl chloride resin seed latex (b) was obtained that had a solid content of 35 wt%, an average particle size of 0.55 μm, and contained 2 wt% of lauroyl peroxide relative to the vinyl chloride resin.
[0040] Synthesis Example 3 1m 3Into an autoclave, 400 kg of deionized water, 350 kg of vinyl chloride monomer, 2 kg of 16 wt% aqueous potassium laurate solution, 5 kg of 16 wt% aqueous sodium dodecylbenzenesulfonate solution, and 7 kg of 2 wt% aqueous potassium persulfate solution were charged, and the temperature was raised to 54° C. to proceed with polymerization. After the pressure was lowered, the unreacted vinyl chloride monomer was recovered to obtain a seed latex (c) having an average particle size of 0.13 μm and a solid content of 42 wt%.
[0041] Manufacturing Example 1 In a 2.5-liter autoclave, 500 g of deionized water, 640 g of vinyl chloride monomer, 160 g of vinyl acetate monomer (20 wt% relative to the total amount of mixed monomers), 9 g of 5 wt% aqueous sodium lauryl sulfate, 85 g of seed latex (a), and 4 g of 0.1 wt% aqueous copper sulfate were charged, and then the temperature of the reaction mixture was raised to 35°C to initiate polymerization, and a 0.05 wt% aqueous ascorbic acid solution was continuously added throughout the entire polymerization time so as to maintain the polymerization temperature, and the polymerization was terminated when the polymerization conversion rate reached 90%. Note that 120 g of a 5 wt% aqueous sodium lauryl sulfate solution was continuously added from the start of polymerization to the end of polymerization.
[0042] The unreacted monomer was then recovered to obtain a latex. The vinyl chloride-vinyl acetate copolymer resin latex (A) for paste processing thus obtained contained 15 wt % of vinyl acetate residue units.
[0043] Manufacturing Example 2 In a 2.5-liter polymerization vessel, 610 g of deionized water, 730 g of vinyl chloride monomer, 24 g of seed latex (a), 50 g of seed latex (b), 120 g of seed latex (c), and 15 g of 5 wt% aqueous solution of sodium dodecylbenzenesulfonate were charged, and then the temperature of the reaction mixture was raised to 61°C to start polymerization, and the polymerization was terminated when the polymerization conversion rate reached 95%. Note that 100 g of 5 wt% aqueous solution of sodium dodecylbenzenesulfonate was continuously added from the start of polymerization to the end of polymerization. Then, unreacted monomers were recovered to obtain vinyl chloride resin latex (B) for paste processing.
[0044] Example 1 In the vinyl chloride-vinyl acetate copolymer resin latex for paste processing (A) obtained in Production Example 1, 5 parts by weight of montmorillonite (Kunipia F (product name); particle size 300 nm, aspect ratio 300, manufactured by Kunimine Industries Co., Ltd.) was dispersed relative to 100 parts by weight of latex solid content, and further spray-dried in a spray dryer at a hot air inlet temperature of 160°C and an outlet temperature of 55°C to obtain vinyl chloride-vinyl acetate copolymer resin particles for paste processing. The results of TEM-EDS elemental analysis of the thin film cross section of the obtained vinyl chloride-vinyl acetate copolymer resin particles for paste processing are shown in Figure 1. It was confirmed that aluminum derived from montmorillonite was present along the outer surface of the vinyl chloride-vinyl acetate copolymer resin particles for paste processing, and that montmorillonite was present as a coating layer on the surface of the particles.
[0045] 100 parts by weight of the obtained vinyl chloride-vinyl acetate copolymer resin particles for paste processing were mixed with 160 parts by weight of diisononyl phthalate, 70 parts by weight of surface-treated calcium carbonate (manufactured by Takehara Chemical Industry Co., Ltd., (product name) NEOLIGHT SP-60), 35 parts by weight of heavy calcium carbonate (manufactured by Nitto Funka Kogyo Co., Ltd., (product name) NN♯500), and 20 parts by weight of a diluent (manufactured by Exxon Mobil Corp., (product name) Exol D80) to obtain a paste PVC resin composition 1. The obtained paste PVC composition 1 was used to measure the viscosity increase rate and evaluate it.
[0046] 100 parts by weight of the obtained vinyl chloride-vinyl acetate copolymer resin particles for paste processing were mixed with 100 parts by weight of diisononyl phthalate, 70 parts by weight of surface-treated calcium carbonate (manufactured by Takehara Chemical Industry Co., Ltd., product name: NEOLIGHT SP-60), 35 parts by weight of heavy calcium carbonate (manufactured by Nitto Funka Kogyo Co., Ltd., product name: NN♯500), and 20 parts by weight of a diluent (manufactured by Exxon Mobil, product name: Exxol D80) to obtain a paste PVC resin composition 2.
[0047] The obtained paste PVC resin composition 2 was applied to a thickness of 2 mm on a release paper and heated at 120°C for 30 minutes to prepare a paste PVC composition sheet. The obtained paste PVC composition sheet was used to measure and evaluate the breaking elongation and breaking strength. The viscosity increase rate was low at 2100%, and the storage stability was excellent. In addition, the breaking elongation when processed at 120°C was 193%, and the breaking strength was 1.8 MPa. The evaluation results are shown in Table 1.
[0048] Example 2 Vinyl chloride-vinyl acetate copolymer resin particles for paste processing were obtained in the same manner as in Example 1, except that the inorganic filler added was saponite (manufactured by Kunimine Kogyo Co., Ltd., product name Sumecton SA; particle size 40 nm, aspect ratio 40) and the amount of inorganic filler added was 0.6 parts by weight per 100 parts by weight of the latex solid content. A TEM-EDS elemental analysis of a thin film cross section of the obtained vinyl chloride-vinyl acetate copolymer resin particles for paste processing was performed, and it was confirmed that aluminum derived from saponite was present along the outer surface of the vinyl chloride-vinyl acetate copolymer resin particles for paste processing, and that saponite was present as a coating layer on the surface of the vinyl chloride-vinyl acetate copolymer resin particles for paste processing.
[0049] Using the obtained vinyl chloride-vinyl acetate copolymer resin particles for paste processing, a composition and a paste PVC composition sheet were obtained in the same manner as in Example 1. The viscosity increase rate was low at 9100%, and the storage stability was excellent. In addition, the breaking elongation when processed at 120°C was 285%, and the breaking strength was 4.3 MPa. The evaluation results are shown in Table 1.
[0050] Example 3 Vinyl chloride-vinyl acetate copolymer resin particles for paste processing were obtained in the same manner as in Example 1, except that the inorganic filler added was plate-like alumina (manufactured by DIC Corporation, (product name) AP05; particle size 4000 nm, aspect ratio 30). TEM-EDS elemental analysis of a thin film cross section of the obtained vinyl chloride-vinyl acetate copolymer resin particles for paste processing confirmed that aluminum derived from the plate-like alumina was present along the outer surface of the vinyl chloride-vinyl acetate copolymer resin particles for paste processing, and that the plate-like alumina was present as a coating layer on the surface of the vinyl chloride-vinyl acetate copolymer resin particles for paste processing.
[0051] Using the obtained vinyl chloride-vinyl acetate copolymer resin particles for paste processing, a paste PVC resin composition and a paste PVC composition sheet were obtained in the same manner as in Example 1. The viscosity increase rate was low at 9000%, and the storage stability was excellent. In addition, the breaking elongation when processed at 120°C was 293%, and the breaking strength was 4.5 MPa. The evaluation results are shown in Table 1.
[0052] Example 4 Vinyl chloride-vinyl acetate copolymer resin particles for paste processing were obtained in the same manner as in Example 1, except that the inorganic filler added was plate-like alumina (manufactured by DIC Corporation, (product name) AP05) and the amount of inorganic filler added was 24 parts by weight relative to 100 parts by weight of the latex solid content. TEM-EDS elemental analysis of a thin film cross section of the obtained vinyl chloride-vinyl acetate copolymer resin particles for paste processing was performed, and it was confirmed that aluminum derived from the plate-like alumina was present along the outer surface of the vinyl chloride-vinyl acetate copolymer resin particles for paste processing, and that the plate-like alumina was present as a coating layer on the surface of the vinyl chloride-vinyl acetate copolymer resin particles for paste processing.
[0053] Using the obtained vinyl chloride-vinyl acetate copolymer resin particles for paste processing, a paste PVC resin composition and a paste PVC composition sheet were obtained in the same manner as in Example 1. The viscosity increase rate was low at 6500%, and the storage stability was excellent. In addition, the breaking elongation when processed at 120°C was 325%, and the breaking strength was 3.5 MPa. The evaluation results are shown in Table 1.
[0054] Example 5 In the vinyl chloride resin latex for paste processing (B) obtained in Production Example 2, 5 parts by weight of montmorillonite (Kunipia F, product name, manufactured by Kunimine Industries Co., Ltd.) was dispersed relative to 100 parts by weight of the latex solid content, and further spray-dried in a spray dryer at a hot air inlet temperature of 160°C and an outlet temperature of 55°C to obtain vinyl chloride resin particles for paste processing. When the obtained vinyl chloride resin particles for paste processing were subjected to TEM-EDS elemental analysis of a thin film cross section, it was confirmed that aluminum derived from montmorillonite was present along the outer surface of the vinyl chloride resin particles for paste processing, and that montmorillonite was present as a coating layer on the surface of the vinyl chloride resin particles for paste processing.
[0055] Using the obtained vinyl chloride resin particles for paste processing, sol kneading was carried out in the same manner as in Example 1 to obtain a paste PVC resin composition and a paste PVC composition sheet. The obtained paste PVC composition and paste PVC composition sheet were evaluated in the same manner as in Example 1. The viscosity increase rate was low at 12%, and the storage stability was excellent. In addition, the breaking elongation when processed at 120°C was 28%, and the breaking strength was 0.5 MPa. The evaluation results are shown in Table 1.
[0056] Example 6 Except for changing the inorganic filler to kaolin (manufactured by Hayashi Kasei Co., Ltd., product name: HydriteN), vinyl chloride-vinyl acetate copolymer resin particles for paste processing were obtained in the same manner as in Example 1. When the obtained vinyl chloride-vinyl acetate copolymer resin particles for paste processing were subjected to TEM-EDS elemental analysis of a thin film cross section, it was confirmed that aluminum derived from kaolin was present along the outer surface of the vinyl chloride-vinyl acetate copolymer resin particles for paste processing, and that kaolin was present as a coating layer on the surface of the vinyl chloride-vinyl acetate copolymer resin particles for paste processing.
[0057] Using the obtained vinyl chloride-vinyl acetate copolymer resin particles for paste processing, a paste PVC resin composition and a paste PVC composition sheet were obtained in the same manner as in Example 1. The viscosity increase rate was low at 9100%, and the storage stability was excellent. In addition, the breaking elongation when processed at 120°C was 337%, and the breaking strength was 3.4 MPa. The evaluation results are shown in Table 1.
[0058] Example 7 Except for using hydrotalcite (manufactured by Toda Kogyo Co., Ltd., product name LT-015D) as the added inorganic filler, vinyl chloride-vinyl acetate copolymer resin particles for paste processing were obtained in the same manner as in Example 1. When the obtained vinyl chloride-vinyl acetate copolymer resin particles for paste processing were subjected to TEM-EDS elemental analysis of a thin film cross section, it was confirmed that aluminum derived from hydrotalcite was present along the outer surface of the vinyl chloride-vinyl acetate copolymer resin particles for paste processing, and that hydrotalcite was present as a coating layer on the surface of the vinyl chloride-vinyl acetate copolymer resin particles for paste processing.
[0059] Using the obtained vinyl chloride-vinyl acetate copolymer resin particles for paste processing, a paste PVC resin composition and a paste PVC composition sheet were obtained in the same manner as in Example 1. The viscosity increase rate was low at 9300%, and the storage stability was excellent. In addition, the breaking elongation when processed at 120°C was 348%, and the breaking strength was 3.7 MPa. The evaluation results are shown in Table 1.
[0060] [Table 1]
[0061] Comparative Example 1 Except for not adding an inorganic filler, paste PVC resin particles were obtained in the same manner as in Example 1. When the obtained paste PVC resin particles were subjected to TEM-EDS elemental analysis of a thin film cross section, no aluminum was observed on the outer surface of the paste PVC resin particles.
[0062] Using the obtained paste PVC resin particles, a paste PVC resin composition and a paste PVC composition sheet were obtained in the same manner as in Example 1. The viscosity increase rate was as high as 12000%. In addition, the breaking elongation when processed at 120°C was 302% and the breaking strength was 4.3 MPa. The evaluation results are shown in Table 2.
[0063] Comparative Example 2 Paste PVC resin particles were obtained in the same manner as in Example 1, except that the inorganic filler added was plate-like alumina (manufactured by DIC Corporation, (product name) AP10; particle size 8000 nm, aspect ratio 15). When the obtained paste PVC resin particles were subjected to TEM-EDS elemental analysis of a thin film cross section, it was confirmed that aluminum derived from the plate-like alumina was present along the outer surface of the paste PVC resin particles, and that the plate-like alumina was present on the surface of the paste PVC resin particles.
[0064] Using the obtained paste PVC resin particles, a paste PVC resin composition and a paste PVC composition sheet were obtained in the same manner as in Example 1. The viscosity increase rate was as high as 12300%. In addition, the breaking elongation when processed at 120°C was 348% and the breaking strength was 3.9 MPa. The evaluation results are shown in Table 2.
[0065] Comparative Example 3 Paste PVC resin particles were obtained in the same manner as in Example 1, except that the inorganic filler added was columnar alumina (manufactured by Kawaken Fine Chemicals Co., Ltd., product name Aluminosol 10A; particle size 50 nm, aspect ratio 5) and the amount of inorganic filler added was 0.6 parts by weight per 100 parts by weight of the latex solid content. When the obtained paste PVC resin particles were subjected to TEM-EDS elemental analysis of a thin film cross section, it was confirmed that aluminum derived from the columnar alumina was present along the outer surface of the paste PVC resin particles, and that the columnar alumina was present on the surface of the paste PVC resin particles.
[0066] Using the obtained paste PVC resin, a paste PVC resin composition and a paste PVC composition sheet were obtained in the same manner as in Example 1. The viscosity increase rate was as high as 10,800%. In addition, the breaking elongation when processed at 120°C was 305% and the breaking strength was 5.0 MPa. The evaluation results are shown in Table 2.
[0067] [Table 2] [Industrial Applicability]
[0068] The vinyl chloride resin particles obtained by the present invention exhibit little change in viscosity over time in the sol, which is a composition when kneaded with a plasticizer, and have excellent storage stability, particularly in environments of 40°C or higher. They also have excellent properties, particularly for use in automobile underbody coatings and automobile sealants, and are therefore of great industrial value.
Claims
1. The vinyl chloride resin particles have an inorganic filler present on the outer surface thereof, the inorganic filler being a plate-like inorganic filler having a particle diameter of 60 to 7,000 nm and an aspect ratio of 20 to 2,000.
2. 2. The polyvinyl chloride resin particles according to claim 1, wherein the inorganic filler is present as a coating layer on the surface of the polyvinyl chloride resin particles.
3. 2. The polyvinyl chloride resin particles according to claim 1, wherein the polyvinyl chloride resin particles are polyvinyl chloride resin particles for paste processing.
4. 2. The vinyl chloride resin particles according to claim 1, characterized in that the vinyl chloride resin particles are vinyl chloride-vinyl acetate copolymer resin particles for paste processing having a vinyl acetate residue content of 1 to 20 wt %.
5. 2. The vinyl chloride resin particles according to claim 1, wherein the plate-like inorganic filler is present in an amount of 0.1 to 25 parts by weight based on 100 parts by weight of the vinyl chloride resin.
6. 2. The vinyl chloride resin particles according to claim 1, wherein the plate-like inorganic filler is at least one selected from the group consisting of montmorillonite, bentonite, saponite, hectorite, plate-like alumina, kaolin, and hydrotalcite.
7. 2. A vinyl chloride resin composition comprising at least 50 to 200 parts by weight of a plasticizer based on 100 parts by weight of the vinyl chloride resin particles according to claim 1.
8. A sheet made of the vinyl chloride resin composition according to claim 7.
9. An automobile underbody coat made of the vinyl chloride resin composition according to claim 7.
10. 8. An automobile sealant made from the vinyl chloride resin composition according to claim 7.
Citation Information
Patent Citations
Production of polyvinyl chloride resin for paste processing
JP1994056915A
Polyvinyl chloride paste resin composition and additive therefor
JP2010241977A